Energy and economic improvement of a domestic refrigerator by replacing its original R12 refrigerant with an ecological one - experimental analysis - Gonzales Chávez, Salome (2014)
We demonstrate experimentally the energy and economic improvement of a domestic refrigerator, after only replace the original refrigerant R-12 (CFC) on the other ecological refrigerant R-134b (HFC). Commonly a refrigerator using CFC is replaced with new green refrigerator. However, in developing countries the residential sector has mostly refrigerators operating with R-12 and life exceeding 10 years use, despite the existence of international agreements that prohibit their use.  As a result we obtain that the refrigerator in evaluating operating with ecological refrigerant, compared with R-12 refrigerant source, stable thermodynamic conditions operation and lower power consumption compressor, for all load conditions and extended periods of operation is achieved. Therefore, one of the most convenient solutions from a socioeconomic view point, it is only replacing CFC refrigerant used in the refrigerator (old), making the appropriate dosage of ecological coolant and lubrication oil-fluidizationKeywords.-